Bioinspired “cage traps” for closed-loop lead management of perovskite solar cells under real-world contamination assessment - Luo, Huaiqing; Li, Pengwei; Ma, Junjie; Li, Xue; Zhu, He; Cheng, Yajie; Li, Qin; Xu, Qun; Zhang, Yiqiang; Song, Yanlin (Nature communications, 2023)
Despite the remarkable progress made in perovskite solar cells, great concerns regarding potential Pb contamination risk and environmental vulnerability risks associated with perovskite solar cells pose a significant obstacle to their real-world commercialization. In this study, we took inspiration from the ensnaring prey behavior of spiders and chemical components in spider web to strategically implant a multifunctional mesoporous amino-grafted-carbon net into perovskite solar cells, creating a biomimetic cage traps that could effectively mitigate Pb leakage and shield the external invasion under extreme weather conditions. The synergistic Pb capturing mechanism in terms of chemical chelation and physical adsorption is in-depth explored. Additionally, the Pb contamination assessment of end-of-life perovskite solar cells in the real-world ecosystem, including Yellow River water and soil, is proposed. The sustainable closed-loop Pb management process is also successfully established involving four critical steps: Pb precipitation, Pb adsorption, Pb desorption, and Pb recycling. Our findings provide inspiring insights for promoting green and sustainable industrialization of perovskite solar cells. Potential lead contamination risk and environmental vulnerability risk impose a significant obstacle for the commercialization of perovskite solar cells. Here, the authors create a biomimetic cage traps to mitigate lead leakage and establish a sustainable closed-loop lead management process.